Learning Motivation and Students’ Achievement in Learning English: A Case Study at Secondary School Students in the Covid-19 Pandemic Situation - Agus Rahardjo; Supratmi Pertiwi (Journal of English Language Teaching and Literature)
The Covid-19 pandemic currently occurring has significantly influenced on the motivation and the learning achievement of students. This study aimed at finding out (1) students’ motivation in learning, and (2) students’ achievement learning English, in the current situation of covid-19 pandemic. By using random sampling technique, this study employed 84 students from the population of 420 students of a senior high school in Surabaya. Data was collected using questionnaires and test, and then was analyzed by using Likert scale and descriptive statistics through SPSS. The research result showed that in the current covid-19 pandemic condition, the correlation between students’ learning motivation and students’ achievement in learning English was classified in to low category (r = 0.22) ranging from 0.200-0.400.